Alcohol consumption and risk of dementia: 11‐year follow‐up of UK Biobank cohort study. (31st December 2021) - Wei, Chang; Zhao, Ziyi; Li, Bingyu; Sha, Feng
Abstract: Background: The negative effect of alcohol consumption on cognitive function is found to be J‐shaped. We analyzed the association between alcohol consumption and the risk of dementia and examined the effect modification by APOE genotypes. Method: 157, 172 Participants with nearly equal alcohol consumption compared with ten years previously were included from UK Biobank cohort study. Levels of alcohol consumption were evaluated on both categorical scales such as abstainers, occasional drinkers, monthly drinkers, light‐to‐moderate drinkers (0‐ 14 units per week), and heavily drinkers (over 14 units per week) and continuous scales (total average weekly units of alcohol consumption), with Cox regression models and restricted cubic splines (RCS). Models over all participants and stratified on APOE genotypes were conducted to assess the risk of dementia, adjusted for sociodemographic, health behaviors, and health‐related variables. Result: 709 (0.45%) out of the 157, 172 participants developed dementia over a mean follow‐up of 11.4 years. Among all participants, abstainers (HR = 1.75, 95% CI 1.25 to 2.45) and occasional drinkers (1.45, 1.03 to 2.02) have an increased risk compared with light‐to‐moderate drinkers, whereas monthly drinkers (0.77, p = 0.25) and heavy drinkers (1.02, p = 0.86) do not show a significant difference. In the stratified analysis, among APOE ɛ4 allele carriers, there's no significant difference between any category of drinkers and mildly weekly drinkers. In RCS with Cox models, 589 (0.44%) out of the 132, 417 participants developed dementia over a mean follow‐up of 11.4 years. A J‐shape association between total average weekly alcohol consumption and dementia incidence was found only among APOE ɛ4 allele non‐carriers. Conclusion: The effect of alcohol consumption on the risk of dementia differs between APOE ɛ4 carriers and non‐carriers. The association between light‐to‐moderate alcohol consumption and dementia will be further examined.